Hawkeye Archery Enterprise / Janet Richel Jeffery ... [et al.] - Jeffery, Janet Richel; Dennis Ding, Joiecy; Neldin, Nelver Jilord; Zain, Muhamnmad Faisal; Awang Omar Ali, Nur Syaza; Jemat, Amanda Hannah (2014)
Marketing is important criteria in business. In simplest form, Marketing is the exchange of something of value between the seller and the buyer. According to Oxford- advanced learner’s dictionary, marketing plan can be defined as the theory and practice of presenting, advertising and selling thing. A marketing plan is a written document that details the necessary actions to achieve one or more marketing objectives. It can be for a product or service, a brand, or a product line. A marketing plan may be part of an overall business plan. Solid marketing strategy is the foundation of a well-written marketing plan. While a marketing plan contains a list of actions, a marketing plan without a sound strategic foundation is of little use. It designed all the activities relating to marketing objectives and the changing of marketing environment. A good management had to be concern and make sure that all plan runs smoothly and achieves its target and goals. It plays an important role to every business in order to make sure all of the business marketing is properly arranged.